A paleontologia no ensino de ciências: uma investigação de professores e estudantes de uma escola da rede estadual de Uruguaiana/RS - (:unkn) unknown (Universidade Federal do Pampa, 2024)
Paleontology is the study of the evolution of life through fossil records, explaining changes or dispersions of these fossils and geological modifications of the planet. Because it has an interdisciplinary nature, this theme can serve as a facilitator in the formation of an integrated and contextualized view of Science. The importance of Paleontology in science education is clear, and despite its weaknesses, it generates great opportunities for the application of dynamic and effective methodologies for teaching and learning. Therefore, the objective of this research was to investigate the perceptions of teachers and students regarding the theme of Paleontology in science education in elementary school II and high school, and the methodologies adopted to approach the theme. This work is characterized by a qualitative and exploratory-descriptive case study. It began with a bibliographic review, focused on analyzing the scientific literature of the last 5 years on the Teaching of Paleontology, based on the collection, analysis and discussion of the data. Next, a field study was conducted, where the participating public were students and teachers of science/biology/geography from the ninth grade of the final years of elementary school and the third year of high school from a school in question. Participation was voluntary for those who were willing to accept the terms of the TCLE and the TALE in the case of minor students. Then, the teachers answered the research questionnaires, which focused on their perceptions regarding Paleontology, how it is approached by the teacher or how the student has contact with the content and whether it lacks presence in the school environment. One questionnaire was applied to the teachers and another to the students, with similar questions; however, with some questions specific to teaching and others to learning. The data obtained were analyzed following Bardin's content analysis method, consisting of a series of techniques to obtain a greater understanding of content through indicators. Thus, it was possible to verify the effectiveness of each approach of the participating teachers in relation to the topic of Paleontology by comparing it with the results of the students. Several methodologies were developed, applied and described as effective among the works selected and analyzed in this research, ensuring a large collection of inspiration for teachers and other researchers in the area. Among the students, it was observed that even with very basic information about paleontology, most of these perceptions came from digital means of dissemination or entertainment media. When investigating the teachers, little could be identified regarding their methodologies even with some emphasis on study groups and interdisciplinary reviews. By comparing the results obtained by the two questionnaires it was possible to diagnose the topic of paleontology in science teaching considering its opportunities for methodological applications. Therefore it is necessary that more research on this topic be developed and applied aiming at greater knowledge and disseminating updated ideas on how to use interdisciplinary themes such as paleontology to teach science.
Paleontology in science teaching: an investigation of teachers and students at a school in the state network of Uruguaiana/RS
Keywords: Paleontology; Ensino de ciências; Aprendizagem de ciências; Paleontologia; Interdisciplinaridade; Science teaching; Science learning; Interdisciplinarity; CIENCIAS HUMANAS